Strengthening the Child Protection Ecosystem through Microlearning: Evaluating Cross-Stakeholder Acceptance - Safira Ryanatami (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2026)
Child protection continues to present significant global and national challenges, with the private sector increasingly recognized as a key actor in promoting and safeguarding children’s rights. However, corporate engagement is often hindered by limited awareness, time constraints, and the lack of accessible, flexible training models. To address these barriers, a microlearning-based e-learning program delivered through a Learning Management System (microlearning-LMS) was developed to strengthen cross-sector professional capacity in child protection. Using a quantitative approach, data were collected through a survey of 136 respondents representing business professionals, non-profit practitioners, government actors, and youth groups, employing purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital learning acceptance is significantly influenced by Perceived Ease of Use—driven by System Quality and prior Experience—and Perceived Usefulness—determined by Content Quality and Information Quality. These results indicate that adult learners differentiate between technical usability considerations and the instrumental value of learning materials. This study contributes to the discourse on community engagement by demonstrating that participatory curriculum design enhances perceived usefulness and technology acceptance. High acceptance of microlearning reflects not only system effectiveness but also cross-sector readiness to integrate child protection principles, ultimately supporting community empowerment and Sustainable Development Goals (SDGs).